Placement of Competency Based Structural Officials in the Youth Sports and Tourism Service of Serang Regency, Banten Province - Ayu, Deva Hartika; Helwani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Competence is one of the important considerations in terms of employee placement in a particular position or position. This is in accordance with the principle of 'the right man on the right place', which means